Intracoronary autologous bone marrow cell transfer after myocardial infarction: the BOOST-2 randomised placebo-controlled clinical trial - Wollert, Kai Christoph; Chorianopoulos, Emmanuel; Katus, Hugo (European heart journal, 2017)
Aims: Intracoronary infusion of autologous nucleated bone marrow cells (BMCs) enhanced the recovery of left ventricular ejection fraction (LVEF) after ST-segment elevation myocardial infarction (STEMI) in the randomised-controlled, open-label BOOST trial. We reassessed the therapeutic potential of nucleated BMCs in the randomised placebo-controlled, double-blind BOOST-2 trial conducted in 10 centres in Germany and Norway. Methods and results: Using a multiple arm design, we investigated the dose–response relationship and explored whether γ-irradiation which eliminates the clonogenic potential of stem and progenitor cells has an impact on BMC efficacy. Between 9 March 2006 and 16 July 2013, 153 patients with large STEMI were randomly assigned to receive a single intracoronary infusion of placebo (control group), high-dose (hi)BMCs, low-dose (lo)BMCs, irradiated hiBMCs, or irradiated loBMCs 8.1 ± 2.6 days after percutaneous coronary intervention (PCI) in addition to guideline-recommended medical treatment. Change in LVEF from baseline (before cell infusion) to 6 months as determined by MRI was the primary endpoint. The trial is registered at Current Controlled Trials (ISRCTN17457407). Baseline LVEF was 45.0 ± 8.5% in the overall population. At 6 months, LVEF had increased by 3.3 percentage points in the control group and 4.3 percentage points in the hiBMC group. The estimated treatment effect was 1.0 percentage points (95% confidence interval, −2.6 to 4.7; P = 0.57). The treatment effect of loBMCs was 0.5 percentage points (−3.0 to 4.1; P = 0.76). Likewise, irradiated BMCs did not have significant treatment effects. BMC transfer was safe and not associated with adverse clinical events. Conclusion: The BOOST-2 trial does not support the use of nucleated BMCs in patients with STEMI and moderately reduced LVEF treated according to current standards of early PCI and drug therapy.